Development and Validation of an RP-HPLC Method for the Quantitative Analysis of Triclosan in Human Urine - Prince Karikari; James Oppong-Kyekyeku; Edmund Ekuadzi; Samuel Oppong Bekoe; Rita Opoku; Daniel Nimako Amprako; Emmanuel Addo-Yobo; Sandra Kwarteng Owusu; Bernard Arhin; Adegoke G. Falade; Ganiyu Arinola; Adeleye S. Bakarey; et al. (Journal of Chemistry)
Triclosan (TCS), a synthesized chlorinated phenolic compound, is commonly utilized in consumable products as an antimicrobial agent. TCS has sparked widespread awareness because of its toxicity and possible negative effect on public health in recent years. In this study, a highly sensitive, fast, and cost-effective isocratic reversed-phase high-performance liquid chromatography (RP-HPLC) method coupled with solid-phase extraction for analysis of triclosan in human urine samples was developed. The method utilized methanol and water in a ratio of 90 : 10 as the mobile phase on a Phenomenex Luna 3 µm C18(2) 100 Å, 150 × 4.60 mm stationary phase, with a runtime of 5 minutes. The method showed good resolution of triclosan in the presence of the sample matrix. Validation of the method was performed according to the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH). Linearity was tested over a range of 0.00625 µg/mL to 6.4 µg/mL, as accuracy recorded a recovery of 89.25%, 91.0%, and 92.75%. Limits of detection (LOD) and quantification (LOQ) were obtained to be 0.0173 µg/mL and 0.0525 µg/mL, respectively. The method proved to be robust over a temperature range of 26°C, 30°C, and 35°C and a flow rate of 0.5 ml, 1.0 ml, and 1.5 ml. The developed method was employed to detect and quantify triclosan in 153 urine samples, comprising 60 samples from Ibadan, Nigeria, and 93 samples from Kumasi, Ghana. Triclosan was detected in a total of 52 samples with an average content of 0.054588 µg/ml. This method can therefore be used for the routine analysis of triclosan in urine samples.